Human antibodies targeting Zika virus NS1 provide protection against disease in a mouse model. Issue 1 (December 2018) - Bailey, Mark; Duehr, James; Dulin, Harrison; Broecker, Felix; Brown, Julia; Arumemi, Fortuna; Bermúdez González, Maria; Leyva-Grado, Victor; Evans, Matthew; Simon, Viviana; Lim, Jean; Krammer, Florian; et al.
Abstract Zika virus is a mosquito-borne flavivirus closely related to dengue virus that can cause severe disease in humans, including microcephaly in newborns and Guillain-Barré syndrome in adults. Specific treatments and vaccines for Zika virus are not currently available. Here, we isolate and characterize four monoclonal antibodies (mAbs) from an infected patient that target the non-structural protein NS1. We show that while these antibodies are non-neutralizing, NS1-specific mAbs can engage FcγR without inducing antibody dependent enhancement (ADE) of infection in vitro. Moreover, we demonstrate that mAb AA12 has protective efficacy against lethal challenges of African and Asian lineage strains of Zika virus inStat2 –/– mice. Protection is Fc-dependent, as a mutated antibody unable to activate known Fc effector functions or complement is not protective in vivo. This study highlights the importance of the ZIKV NS1 protein as a potential vaccine antigen. Zika virus infection can cause severe disease in humans and there are currently no specific treatments or vaccines. Here, Baileyet al . isolate antibodies recognizing non-structural protein NS1 and show that they protect mice from disease by an Fc-dependent, non-neutralizing mechanism.